Validating a global rating scale to monitor individual resident learning curves during arthroscopic knee meniscal repair. - Alvand, A; Logishetty, K; Middleton, R; Khan, T; Jackson, W; Price, A; Rees, J (2013)
PURPOSE: To determine whether a global rating scale (GRS) with construct validity can also be used to assess the learning curve of individual orthopaedic trainees during simulated arthroscopic knee meniscal repair. METHODS: An established arthroscopic GRS was used to evaluate the technical skill of 19 orthopaedic residents performing a standardized arthroscopic meniscal repair in a bioskills laboratory. The residents had diagnostic knee arthroscopy experience but no experience with arthroscopic meniscal repair. Residents were videotaped performing an arthroscopic meniscal repair on 12 separate occasions. Their performance was assessed by use of the GRS and motion analysis objectively measuring the time taken to complete tasks, path length of the subject's hands, and number of hand movements. One author assessed all 228 videos, whereas 2 other authors rated 34 randomly selected videos, testing the interobserver reliability of the GRS. The validity of the GRS was tested against the motion analysis. RESULTS: Objective assessment with motion analysis defined the surgeon's learning curve, showing significant improvement by each subject over 12 episodes (P < .0001). The GRS also showed a similar learning curve with significant improvements in performance (P < .0001). The median GRS score improved from 15 of 34 (interquartile range, 14 to 17) at baseline to 22 of 34 (interquartile range, 19 to 23) in the final period. There was a moderate correlation (P < .0001, Spearman test) between the GRS and motion analysis parameters (r = -0.58 for time, r = -0.58 for path length, and r = -0.51 for hand movements). The inter-rater reliability among 3 trained assessors using the GRS was excellent (Cronbach α = 0.88). CONCLUSIONS: When compared with motion analysis, an established arthroscopic GRS, with construct validity, also offers a moderately feasible method to monitor the learning curve of individual residents during simulated knee meniscal repair. CLINICAL RELEVANCE: An arthroscopic GRS can be used for monitoring skill improvement during knee meniscal repair and has the potential for use as a training and assessment tool in the real operating room.